The level and regional differentiation of Poland’s GDP in the interwar period - Witold Maciej Orłowski (Ekonomista, 2023)
The article estimates the level of GDP per capita in the Second Polish Republic in 1938, both for the entire country and for individual voivodeships. The calculations take as their starting point Maddison’s historic estimates of GDP produced in the territory that now constitutes Poland, together with Polish and German statistical data from the interwar period. First, the results show that Poland’s GDP per capita in 1938 was significantly lower than that of Western Europe and the rapidly industrializing Soviet Union. Second, they allow differences in regional development to be assessed on the basis of the size and composition of GDP, the sharpness of the dichotomy between Poland A and Poland B, and a comparison of Poland’s regional problems vis-à-vis those of other large European countries, especially Italy. The scale of regional differences in GDP per capita, which exceeded 3 to 1, was not abnormally high compared to other large European countries. The problem, however, was that most of Poland’s population lived in underdeveloped areas and were dependent on agriculture while only a small minority lived in industrialized areas.